(untitled) (Bangladesh Rice Journal, 2018)
This study was conducted in all 25 upazilas of Chittagong Hill Tracts during 2016 using a pre-designed and pre-tested semi-structured questionnaire for documenting the existing cropping pattern, crop diversity and cropping intensity. Boro-Fallow-T. Aman was the most dominant cropping pattern in Chittagong Hill Tracts (15.06%) existed in all upazilas except Ruma of Bandarban. Single T. Aman cropping pattern ranked the second position (13.67%) distributed in 21 upazilas. Shifting or zhum cultivation was the third cropping pattern in the region (9.24%) distributed to 20 upazilas. Only Rabi vegetables was recorded as the fourth cropping pattern (4.90%) covered 17 upazilas. Vegetables- Fallow-T. Aman cropping pattern ranked fifth (4.23%) in the region and was reported in 22 upazilas. About 30% area was covered by the annual crops mainly with fruits like banana, pineapple and papaya and, spices like ginger and turmeric. The highest number of cropping patterns was recorded in Lama (30) of Bandarban followed by Dighinala (28) of Khagrachhari. The lowest was reported in Ruma (8) of Bandarban. The overall crop diversity index (CDI) for the region was 0.96. The highest CDI was in Rowangchhari (0.99) of Bandarban followed by Lama (0.96) of Bandarban and the lowest in Belaichhari (0.82) of Rangamati. The single, double and triple cropped area in the region was 33.3%, 32.1% and 3.1% of the net cropped area. The average cropping intensity (CI) of the Chittagong Hill Tracts was 139%, the lowest in Ruma (100%) of Bandarban and the highest in Manikchhari and Panchhari (164%) of Khagrachhari. Bangladesh Rice j. 2017, 21(2): 173-184